Backyard detective : critters up close - Bishop, Nic, 1955- (New York : Scholastic Press, 2002)
Describes a variety of animals and insects that can be found close to home and offers tips on how to observe them.
Includes index.
School Library Journal.
Kirkus Review.
Library Media Connection.
4.9
K-3
Keywords: Urban animals -- Juvenile literature; Animals; Insects; Animals; Insects; Animals; Insects